Solvothermal synthesis of enneanuclear [CuII7LnIII2] clusters. Issue 46 (29th October 2015) - Canaj, Angelos B.; Tzimopoulos, Demetrios I.; Otręba, Marta; Lis, Tadeusz; Inglis, Ross; Milios, Constantinos J.
Abstract : Four enneanuclear heterometallic copper–lanthanide [CuII7LnIII2] (Ln = Gd, Tb, Dy and Y) complexes were isolated and characterized by magnetic measurements. Abstract : Employment of H3 L (= 2-(β-naphthalideneamino)-2-hydroxymethyl-1-propanol) in mixed-metal copper-lanthanide cluster chemistry has led to the isolation of four new enneanuclear heteronuclear isostructural [CuII7LnIII2] complexes. More specifically, the solvothermal reaction of Cu2 (OAc)4 ·2H2 O with H3 L and the corresponding lanthanide nitrate salt in MeCN in the presence of a base, NEt3, yielded three complexes with the general formula [CuII7LnIII2(L)4 (HL)2 (OAc)4 ]·2MeCN (Ln: Gd, 1 ·2MeCN; Tb, 2 ·2MeCN; Dy, 3 ·2MeCN), while in addition the Y III analogue, [CuII7YIII2(L)4 (HL)2 (OAc)4 ]·2MeCN (4 ·2MeCN), was also synthesized in the same manner. The structure of the cluster describes two corner-sharing [Cu3 Ln] cubane metallic units, each one further connected to one Cu II ion. Dc magnetic susceptibility studies in the 5–300 K range for complexes1–4 reveal the presence of both ferromagnetic and antiferromagnetic exchange interactions within the metallic clusters.